2003
DOI: 10.1093/rheumatology/keg028
|View full text |Cite
|
Sign up to set email alerts
|

Is thiopurine methyltransferase genetic polymorphism a major factor for withdrawal of azathioprine in rheumatoid arthritis patients?

Abstract: In this observational study, the absence of response, probably due to the low-dose scheme used, was the major cause of AZA withdrawal in our series of RA patients. TPMT genotyping may allow the use of high doses of AZA in patients with normal TPMT alleles to improve the efficacy of this immunosuppressive drug. Our data support the relationship between gastrointestinal intolerance and thiopurine metabolic imbalance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Corominas et al [29] observed that RA patients carrying the mutant TMPT*3A allele experienced more ADEs with AZA treatment, although this could not statistically be confirmed because of low frequency of mutant carriers.…”
Section: Genetic Overview Of Dmardsmentioning
confidence: 95%
“…Corominas et al [29] observed that RA patients carrying the mutant TMPT*3A allele experienced more ADEs with AZA treatment, although this could not statistically be confirmed because of low frequency of mutant carriers.…”
Section: Genetic Overview Of Dmardsmentioning
confidence: 95%
“…Three of the six patients who discontinued the drug due to severe gastrointestinal side effects such as nausea and vomiting were heterozygous for the TPMT n 3A allele, the remainder had the wild-type TPMT allele. Analysis of patients with and without toxicity compared to those with and without the polymorphisms showed a significant difference (P ¼ 0.018), giving a positive predictive value for a carrier of a TPMT polymorphism of 60% [Corominas et al, 2003]. …”
Section: Pharmacogenetics Of Azathioprinementioning
confidence: 99%
“…The percentages of heterozygous carriers of the mutant allele of the TPMT gene ranged from 6.3% to 9.5%. 25 In addition to the variant alleles associated with significantly decreased levels of TPMT activity, the number of repeat elements in the polymorphic variable number of tandem repeats (VNTR) located in the 5Ј-flanking region of the TPMT promoter gene could modulate levels of enzymatic activity. In the series of Hibi et al, 1 bonemarrow suppression induced by 6-MP and azathioprine was closely related to TPMT mutation.…”
Section: Role and Toxicity Of 6-mp And Azathioprine In The Treatment mentioning
confidence: 99%